Cyclic AMP-independent ATF family members interact with NF-kappa B and function in the activation of the E-selectin promoter in response to cytokines. - Kaszubska, W (1993)
We previously reported that NF-kappa B and a complex we referred to as NF-ELAM1 play a central role in cytokine-induced expression of the E-selectin gene. In this study we identify cyclic AMP (cAMP)-independent members of the ATF family binding specifically to the NF-ELAM1 promoter element. The NF-ELAM1 element (TGACATCA) differs by a single nucleotide substitution from the cAMP-responsive element consensus sequence. We demonstrate that this sequence operates in a cAMP-independent manner to induce transcription and thus define it as a non-cAMP-responsive element (NCRE). We show that ATFa is a component of the NF-ELAM1 complex and its overexpression activates the E-selectin promoter. In addition, ATFa, ATF2, and ATF3 interact directly with NF-kappa B in vitro, linking two unrelated families of transcription factors in a novel protein-protein interaction. Furthermore, we demonstrate that the ability of overexpressed NF-kappa B to transactivate the E-selectin promoter in vivo is dependent on the NF-ELAM1 complex. Our results suggest that a direct interaction between ATFs and NF-kappa B is, at least in part, the mechanism by which these factors specifically regulate E-selectin promoter activity.